Identifying support needs of Maori students enrolled extramurally at Massey University - Barbara Brookfield; Louise MacFarlane (Flexible Learning Association of New Zealand, 2012)
The purpose of this preliminary research project is to develop an overview of the difficulties which extramural Maori students in Hawkes Bay and Poverty Bay encounter. This information will be useful in deciding on the allocation of resources for meeting student support needs in the future.